The Presbyterian magazine: January, 1858;Volume 8(1858) - Armstrong, George D.; Van Rensselaer, Cortlandt (W.H. Mitchell, 1858)
Three letters to a conservative : letter 1 : Dr. Armstrong's letter to Dr. Van Rensselaer on the proper statement of the scripture doctrine of slavery -- Three conservative replies : letter 1 : Dr. Van Rensselaer's reply to Dr. Armstrong on the proper statement of the scripture doctrine of slavery.